1999
DOI: 10.1089/oli.1.1999.9.515
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylenimine but Not Cationic Lipid Improves Antisense Activity of 3′-Capped Phosphodiester Oligonucleotides

Abstract: Lipofectin, which is a mixture of neutral lipid with a cationic lipid, has been widely used to enhance cellular delivery of phosphorothioate, 2'-sugar-modified, and chimeric antisense oligonucleotides. Phosphodiester oligonucleotides delivered with Lipofectin usually do not elicit antisense activity probably because cationic lipid formulations do not sufficiently protect unmodified oligonucleotides from nuclease degradation. We show that a cationic polymer, polyethylenimine (PEI), improves the uptake and antis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 25 publications
(25 reference statements)
4
25
0
Order By: Relevance
“…Polyplexes formed by complexation of PEI and nucleic acids have shown efficient in vitro delivery of DNA [111], ODN [183] and siRNA [184] in various cell lines. In vivo, these polyplexes also displayed antitumoral activity after subcutaneous or intraperitoneal administration, as shown with a siRNA targeted against the growth factor pleiotrophin [185] and the HER-2 receptor [186] in murine subcutaneous tumor models.…”
Section: Delivery Of Nucleic Acidsmentioning
confidence: 99%
“…Polyplexes formed by complexation of PEI and nucleic acids have shown efficient in vitro delivery of DNA [111], ODN [183] and siRNA [184] in various cell lines. In vivo, these polyplexes also displayed antitumoral activity after subcutaneous or intraperitoneal administration, as shown with a siRNA targeted against the growth factor pleiotrophin [185] and the HER-2 receptor [186] in murine subcutaneous tumor models.…”
Section: Delivery Of Nucleic Acidsmentioning
confidence: 99%
“…PEI is a polycation that is widely used to deliver nucleic acids, including DNA (13), siRNA (14Y17), ribozymes (18,19), and oligonucleotides (13,20). The prevailing hypothesis is that the positively charged amine groups of PEI electrostatically complex with the negatively charged phosphate groups of nucleic acids to produce a neutral or positively charged complex with sufficient stability to allow intracellular delivery of the genetic material.…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that the PBAE polymers deliver PSODNs in a different way than PO-ODNs, with the PO-ODNs being more easily released. It has been reported that other polymers like poly-ethylene-imine (PEI) also formed stronger complexes with PS-ODNs when compared to PO-ODNs, which could explain the difference in the release profile (24). From time to time, PS-ODNs could be found in the nuclei of the cells, although not as frequently as the PO-ODNs (data not shown).…”
Section: Intracellular Distribution and Integrity Of Po-and Ps-odns Dmentioning
confidence: 96%